Parameter Psikometri Alat Ukur Strengths and Difficulties Questionnaire (SDQ) - istiqomah istiqomah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
SDQ (Strengths and Difficulties Questionnaire) is a psychological scale to screen the Strengths and Difficulties the special student, emotional and behavioral problem, and school readiness. This adaptation of SDQ aims to test the psychometric parameter: validity, reliability and confirmatory factor analysis. The study was conducted to 153 subjects with the help of significant others in inclusive school and the center of autism at Malang. The analysis indicated 7 invalid items with reliability 0,759. The confirmatory factor analysis showed that all of factor give 54,943 % contribution to the construct of SDQ.